SHOPPING MOTIVATIONS AND THEIR INFLUENCE ON SHOPPING EXPERIENCE IN SUNRISE MALL MOJOKERTO - Cucu Hayati (Media Mahardhika, 2019)
The main focus of this study is shopping motivation. In particular, the study aims to investigate the relationship between shopping motivation of shoppers and the experience of shoppers when shopping in Sunrise Mall. This study explores shopping motivation by examining their hedonic and utilitarian motivations behind shopping and cross-analyzing it with social characteristic the society. By clustering the shopping motivation of shopper in Sunrise Mall, we will understand what kind of experience the visitors need and hope to be realized while doing shopping. The methodology of this study is quantitative analysis, as the research problems are exploratory in nature and rely on deductive inquiry. The survey activities were held on weekdays and weekend. The correspondent analysis was done through Cross-tabulation Analysis and Cluster Analysis using â€œK-Means Clusterâ€ method through SPSS 21. The research brings up the indication that shopper in Sunrise Mall Mojokerto have high motivation as hedonic buyer. Results showed inner city consumers to have higher hedonic motivations for shopping compared to outer city consumers. The findings suggest that Sunrise Mall provides as an important outlet or tenants for inner city consumers who have stronger tendencies to find experiences such as entertainment, intellectual stimulation, and social gathering.Cluster analysis for hedonic and utilitarian shopping motivations produced five consumer clusters: (1). Recreational Shopper, (2). Economic Shopper, (3). Ethical Shopper, (4). Personalized Shopper and (5). Apathetic Shopper.